KEJADIAN GIZI KURANG PADA BALITA - Afriza, Renita; Herawati, Nurul; Suhardono, Suhardono; Alfiah, Alfiah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Toddlerhood is a critical phase in a child's life, characterized by rapid growth and development. The results of an initial survey conducted by researchers in July 2023 on 10 mothers of toddlers in the Lubuk Buaya Health Center working area, showed that 6 out of 10 mothers of toddlers (60%) reported that their children experienced poor nutritional status. The purpose of the study was to determine the factors that cause the incidence of malnutrition in toddlers. The research design used in this study was cross sectional. The research was conducted in the Lubuk Buaya Health Center area. The research was conducted in July 2023. The study population was toddlers (12-59 months) in the Lubuk Buaya Health Center work area which amounted to 243 toddlers. The sample amounted to 80 respondents. The sampling technique used Simple random sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between maternal knowledge (p value: 0.025) and income (p value: 0.010) to the incidence of undernutrition. It is recommended to further improve information sources for mothers of toddlers about the incidence of nutritional status in children and causative factors by conducting regular health counseling and by distributing leaflets or sticking posters at the health center about the importance of checking nutritional status in children under five years of age 12-59 months.Keywords: Undernutrition, Maternal Knowledge, Income.